PENGARUH CAMPURAN BAHAN BAKAR SOLAR DENGAN BIODIESEL MINYAK LEMAK SAPI (BEEF TALLOW) TERHADAP KONSUMSI BAHAN BAKAR PADA MESIN DIESEL (Department of Mechanical Engineering, Faculty of Engineering, Universitas Negeri Semarang, 2021)
This study aims to determine the effect of biodiesel concentration added to each variation of fuel mixture to fuel consumption in diesel motor. Variations of fuel mix between diesel and biodiesel are used B0, B5, B10, B15 and B20 While engine variations are used for 2000, 3000, 4000 rpm.The method used in this research is experiment. The production process of biodiesellemak cattle using transesterification method. Testing fuel consumption using buret. Then concludes the results of research in the form of tables and graphic. The B20 mixture is the most efficient mixture. Five variations of B20 rotation produce the lowest average fuel consumption average of 1,410 kg / hour, while for B0 the highest average fuel consumption is 1,860 kg / hour. The resulting power yield of B20 mixture produces an average power of 47,20 kW compared to pure diesel generating power of 49,86 kW. Larger than the B20 mixture, but the torsion yields the largest average on the B5 mixture of 78,7 Nm.